Austerity measures in crisis countries: Results and impact on mid-term development - Vassilis Monastiriotis; Niamh Hardiman; Aidan Regan; Chiara Goretti; Lucio Landi; J. Ignacio Conde-Ruiz; Carmen Marín; Ricardo Cabral (Intereconomics, 2013)
Since the onset of the sovereign debt crisis, the crisis-stricken countries in Europe have been pushed to take drastic steps to consolidate their finances and reduce their budget deficits. Despite strong public opposition and largely damaging short-run effects, the countries have undertaken many of the internationally recommended/mandated reforms and spending cuts. In this Forum, authors from Greece, Ireland, Italy, Spain and Portugal report on the fiscal consolidation achieved in their respective countries - and the sacrifices that have made it possible. Furthermore, the authors detail what remains to be done to resolve the crisis.
Keywords: 330; Öffentliche Schulden; Haushaltsdefizit; Haushaltskonsolidierung; Haushaltskonsolidierung; Wirkungsanalyse; Europa